2016
DOI: 10.3109/13880209.2015.1127979
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of Hypericum connatum on stress-induced escape deficit in rat is related to its flavonoid content

Abstract: De Feo (2016) The protective effect of Hypericumconnatum on stress-induced escape deficit in rat is related to its flavonoid content, Pharmaceutical Biology, 54:9, 1782-1792, DOI: 10.3109/13880209.2015 Objective This study evaluates the antidepressant-like effect of H. connatum in rats and identifies the components involved in this activity. Materials and methods First, the effects of acute and 14-d oral administrations of an extract derived from H. connatum aerial parts were studied using the Escape Deficit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Several studies also demonstrated that various SJW extracts could reduce stress-induced behavioural deficits in the learned helplessness test (Bhattacharya, Chakrabarti, & Chatterjee, 1998;Chatterjee et al, 1998;Gambarana et al, 1999;Scheggi et al, 2016). The effect on cognition ability was tested in Barnes maze or Morris water maze.…”
Section: Behavioural Pharmacology Related To Antidepressant Effectsmentioning
confidence: 99%
“…Several studies also demonstrated that various SJW extracts could reduce stress-induced behavioural deficits in the learned helplessness test (Bhattacharya, Chakrabarti, & Chatterjee, 1998;Chatterjee et al, 1998;Gambarana et al, 1999;Scheggi et al, 2016). The effect on cognition ability was tested in Barnes maze or Morris water maze.…”
Section: Behavioural Pharmacology Related To Antidepressant Effectsmentioning
confidence: 99%
“…olympicum , and H . adenotrichum , among others [ 3 5 ], mainly studying their biological activity. Phenolic compounds usually account for many of the bio(chemical) properties of plant extracts, so exhaustive investigation of the phytochemical composition of the plant extracts is mandatory.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that quercetin may be considered as a partially useful supplement for the treatment of diabetic depression, and the antidepressant-like properties of quercetin seem to be independent of the HPA axis. Furthermore, Scheggi et al [ 106 ] reported antidepressant activity of Hypericum perforatum L. (Hypericaceae) related to the flavonoid components of this species including quercetin. Also, Rinwa and Kumar [ 107 ] have shown that quercetin suppresses the microglial neuroinflammatory response and induces the antidepressant-like effect in olfactory bulbectomized rats.…”
Section: Resultsmentioning
confidence: 99%